Determination of Accretion Rate in the Body by External Measurements of 47Ca in the Human Forearm Using the Generalized Bauer-Carlsson-Lindquist (BCL) Equation - Harmut, Magda (Nuklearmedizin - NuclearMedicine, 1974)
The index of the mineralization rate AF from the generalized BCL equation was calculated using single-point retention values obtained in the human forearm and plasma after intravenous application of 47Ca. The time-dependent values were compared to the classical Bauer values obtained for day 3 and 6. Numerically equal values were obtained with the Bauer time-invariant ones for day 4.5. The aF (BCL time-invariant) values were correlated to the AF (4.5 day) value and a correlation coefficient of 0.963 was obtained